PRETIBIAL MYXEDEMA: PATHOGENETIC FEATURES AND CLINICAL ASPECTS - Ismoilov, Jamshid Abduraimovich; Egamberdiyeva , Yulduz Komiljon kizi; Mahmamuradova , Nargiza Negmatullayevna; Daminov, Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
Pretibial myxedema (PM), or thyroid dermopathy, is a rare extrathyroidal manifestation of Graves’ disease (GD). The condition is accompanied by mucinous skin changes, mainly in the area of ​​the anterior surface of the leg. Severe forms can lead to lymphatic congestion and disability. It is assumed that long-term and intense autoimmune aggression is necessary for the manifestation of PM. However, data on the role of antibodies to the TSH receptor in the genesis of PM are very controversial. Recently, indications have emerged that IGF-1 receptors are involved in the pathogenesis of this manifestation of HD. In typical cases, PM is localized on the anterior and lateral surfaces of both legs and has a diffuse, tumor, plaque-like or elephantine form. Early diagnosis comes down to regular preventive examination of the pretibial area. A diagnostic biopsy is indicated only in doubtful cases. Maintaining euthyroidism, quitting smoking, avoiding injury, and wearing tight shoes that impair lymphatic drainage can reduce the risk of developing PM in patients with GD. Currently, there are no generally accepted clinical guidelines for the diagnosis and treatment of thyroid dermopathy. This review provides the latest information on the etiopathogenesis of PM and the management of patients with this pathology.